Pengaruh Temperatur Dan Waktu Penahanan Terhadap Sifat Mekanik Dan Struktur Mikro Pada Baja Karbon Rendah - Rhaka Qudzsy Wening Praja; Iman Saefulloh; Agus Pramono (Jurnal Teknik Mesin, 2020)
Basically the characteristic of steel products that is widely used in the construction process is structural steel. In order to compete with structural steel foreign-made, a standards compliance is a minimum requirement that must be done. To meet the JIS G 3302 grade SGC 400 standard, the results of the cold rolled process and continued with Cyclic Spheroidizing on 0,11% carbon steel, resulted in an elongation value that met the standards, but the yield strength and tensile strength were below standard. So that a heat treatment process substitution is needed so that 0,11% carbon steel can meet the JIS G 3302 SGC 400 standards. The aim of this research is to determine the effect of temperature and holding time with the cyclic treatment method on the microstructure and mechanical properties of 0,11 steel % carbon. Also in this research , 0,11% carbon steel was subjected to a heat treatment process with a 3-cyclic method at temperatures of 575, 625, 675°C, then cooled in air blower then given a holding time of 4, 6, 8 minutes. Then 0,11% carbon steel was subjected to tensile test, Vickers hardness test and scanning electron microscope as well as energy dispersive spectroscopy-Mapping. From the temperature variation of 625°C with the cooling medium of the blower produces mechanical properties that meet the JIS G 3302 SGC 400 standard.